Seasonal upsurge of pneumococcal meningitis in the Central African Republic - Crellen, Thomas (Wellcome Open Res, 2019)
A high incidence of bacterial meningitis was observed in the Central African Republic (CAR) from December 2015 to May 2017 in three hospitals in the northwest of the country that are within the African meningitis belt. The majority of cases were caused by Streptococcus pneumoniae (249/328; 75.9%), which occurred disproportionately during the dry season (November-April) with a high case-fatality ratio of 41.6% (95% confidence interval [CI] 33.0, 50.8%). High rates of bacterial meningitis during the dry season in the meningitis belt have typically been caused by Neisseria meningitidis (meningococcal meningitis), and our observations suggest that the risk of contracting S. pneumoniae (pneumococcal) meningitis is increased by the same environmental factors. Cases of meningococcal meningitis (67/328; 20.4%) observed over the same period were predominantly group W and had a lower case fatality rate of 9.6% (95% CI 3.6, 21.8%). Due to conflict and difficulties in accessing medical facilities, it is likely that the reported cases represented only a small proportion of the overall burden. Nationwide vaccination campaigns in the CAR against meningitis have been limited to the use of MenAfriVac, which targets only meningococcal meningitis group A. We therefore highlight the need for expanded vaccine coverage to prevent additional causes of seasonal outbreaks.